2016
DOI: 10.1590/1807-3107bor-2016.vol30.0027
|View full text |Cite
|
Sign up to set email alerts
|

Volume of sealer in the apical region of teeth filled by different techniques: a micro-CT analysis

Abstract: Abstract:The volume of sealer in the apical 1 mm of teeth filled using different techniques was evaluated by micro-commuted tomography (micro-CT). Sixty-four maxillary central incisors were prepared using NiTi rotary instruments. Teeth were randomly distributed into four groups according to root canal sealers (AH Plus, Endofill, Sealapex, and Sealer 26) and subdivided into two subgroups according to the filling techniques (active and passive lateral condensation; n = 8 each). Subsequently, teeth were examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Micro-CT is an innovative tool that provide high-resolution 3-dimensional evaluation of root canal fillings, allowing further exploration of precise internal structures of the sealers in a nondestructive way 20 . For this reason, micro-CT is considered as the gold standard for the filling analysis 21 . Based on this important characteristic to an accurate evaluation, Tanomaru-Filho et al 7 proposed a new technique for assessing flow and filling of root-end filling materials using micro-CT imaging.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Micro-CT is an innovative tool that provide high-resolution 3-dimensional evaluation of root canal fillings, allowing further exploration of precise internal structures of the sealers in a nondestructive way 20 . For this reason, micro-CT is considered as the gold standard for the filling analysis 21 . Based on this important characteristic to an accurate evaluation, Tanomaru-Filho et al 7 proposed a new technique for assessing flow and filling of root-end filling materials using micro-CT imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Araujo et al 21 used micro-CT to evaluate AH Plus, Sealapex and Endofill regarding their volume in the 1 mm apical third after obturation of the teeth. In this study, the lowest volume of sealer was observed in teeth filled with Sealapex and Endofill.…”
Section: Discussionmentioning
confidence: 99%
“…28 In contrast, from the nano-CT results, when a voxel-resolution of 1.58 µm was achieved, it was found that an obvious increase of void fraction and void volume in AH Plus, compared with the bioceramic sealers. This was consistent with a previous finding, which reported underestimation of void volume while using lower resolution micro-CT. 29 Even although micro-CT is considered as the gold standard for analysis of filling quality, 30 the evidence from this birpublications.org/dmfr Evaluation of sealer filling quality using micro-CT and nano-CT Huang et al study has suggested that there might be a threshold of voxel-resolution for the quantitative analysis of voids of endodontic sealers by 3D imaging tools.…”
Section: Discussionmentioning
confidence: 99%
“…Micro-computed tomography (micro-CT) has allowed new perspectives for endodontic research (9), especially to the studies on the factors related to the induction of dentinal microcracks. This technology makes it possible to investigate the presence of dentinal defects with a detailed resolution before and after canal preparation without sectioning the specimens (10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%